IMPLEMENTATION OF THE NATIONAL COMMUNITY EMPOWERMENT PROGRAM (PNPM) IN PONTIANAK - Sri Maryuni (Spirit Publik: Jurnal Administrasi Publik, 2015)
The unsuccessful implementation of national community empowerment program in urban areas (in Indonesia: PNPM) is due to many factors; both internal and external factors. This study aims to acquire insight and understanding a new concept of public policy implementation by applying qualitative descriptive methods. The implementation of PNPM program was involving many elements including: implementer, the program itself, the target groups and environment. The results revealed that the unsuccessful implementation of PNPM in Pontianak was caused by the idealized policy (program), the target groups, the implementing organization (implementer) and environmental factors. The four factors mentioned before were interrelated and influenced each other to form a policy cycle. In implementing this program, the approach used was the empowerment of communities to establish independence of the community and local government agencies that were facilitated by community self-reliance organization. In reality it is very difficult to encourage the poor to participate in the planning and implementation of this empowerment program. For that reason, the community volunteers had to work hard to gain the aspirations of poor communities through Citizen Preparation Meeting (in Indonesia: Rembug Kesiapan Warga) and Development Planning Meeting (in Indonesia: Musyawarah Perencanaan Pembangunan). Keywords: Implementation, Empowerment, Independence, Voluntary